Lesbianism: Deconstructing the Christian church and social hierarchies in South Africa - L. Joubert (Acta Theologica)
Christianity places a high value on one’s faith in Jesus Christ, and from this belief, one fosters a perception of LGBTQI people. The general patriarchal idea that the only true, biblical sexual orientation is heterosexuality is one of the elements contributing to the religious obstacle the LGBTQI face. Lesbian[1] spouses and their children are frequently subjected to animosity and rejection from members of the local community, where they choose to participate in religious activities. This is because lesbians and/or lesbian families depart from the so-called heterosexual norm. To analyse how the Christian church refers to homosexuality. I will use Michel Foucault’s philosophy on discourse and power as a theoretical underpinning to examine the preconceived concept of a fixed social hierarchy within the Christian church and society. The paper focuses on the biblical discourses that underlie lesbian identity. By highlighting how colonial impressions resulted in a homophobic reception of the bible, I argue for a positive reimagining between churches and the LGBTQI community and provide evidence that the Christian church and social hierarchies impact lesbian identity negatively through the implementation of the Biblical text and patriarchal ontology.